Isolation and Characterization of Bacillus Sp. Capable of Degradating Alkali Lignin - Yang, Jing; Zhao, Jian; Jiang, Jianchun; Xu, Hao; Zhang, Ning; Xie, Jingcong; Wei, Min (Frontiers in Energy Research, 2021)
Alkali lignin-degrading Bacillus were isolated from forest soils in China and were identified as Bacillus subtilis TR-03 and Bacillus cereus TR-25 by 16S rDNA sequence analysis. Wherein TR-03 displayed optimal 26.72% alkali lignin (2 g/L) degradation at 7 days and 71.23% of Azure-B (0.01%) decolorization at 36 h of cultivation at 37°C. Ligninolytic enzyme analysis revealed that TR-03 was capable of depolymerizing alkali lignin effectively by the producing of lignin peroxidase and laccase, wherein higher laccase activity was cell-associated. At last, the physical and chemical changes of lignin via SEM and FTIR analysis was further observed to prove the lignin degradation by Bacillus subtilis TR-03.